Targeting STAT3 enhances NDV‐induced immunogenic cell death in prostate cancer cells. Issue 7 (26th February 2020) - Wang, Xueke; Shao, Xiaoyan; Gu, Linaer; Jiang, Ke; Wang, Sitong; Chen, Jianhua; Fang, Juemin; Guo, Xianling; Yuan, Min; Shi, Ji; Ding, Chan; Meng, Songshu; et al.
Abstract: Oncolytic Newcastle disease virus (NDV) induces immunogenic cell death (ICD), liberating danger‐associated molecular patterns (DAMPs) that provokes defiance in neoplastic malignancy. The present study aims to investigate whether and how oncolytic NDV triggers ICD in prostate cancer cells. We show that NDV/FMW, an oncolytic NDV strain FMW, elicited the expression and release of several ICD markers, that is calreticulin (CRT), heat shock proteins (HSP70/90) and high‐mobility group box 1 (HMGB1), in prostate cancer cells. Furthermore, pharmacological repression of apoptosis, necroptosis, autophagy or endoplasmic reticulum (ER) stress exerted diverse effects on the HMGB1 and HSP70/90 evacuation in NDV/FMW‐infected prostate cancer cells. Moreover, ICD markers induced in prostate cancer cells upon NDV/FMW infection, were enhanced by either treatment with a STAT3 (signal transducer and activator of transcription 3) inhibitor or shRNA‐mediated knockdown of STAT3. In nude mice bearing prostate cancer cell‐derived tumours, the tumours injected with the supernatants of NDV/FMW‐infected cells grew smaller than mock‐treated tumours. These results indicate that oncolytic NDV provokes the expression of ICD makers in prostate cancer cells. Our data also suggest that a combination of inhibition of STAT3 with oncolytic NDV could boost NDV‐based anti‐tumour effects against prostate cancer.